Iatrogenic Perforation of Upper Pouch in Pure Esophageal Atresia: A Rare Complication and Review of Literature - Sandesh Parelkar; Dinesh Mundada; Prashant Joshi; Beejal Sanghvi; Satish Kapadnis; Sanjay Oak (Georg Thieme Verlag KG, 2013)
Abstract Iatrogenic perforation of the neonate's pharynx and esophagus with normal anatomy was first described by Eklöf et al in 1968. It typically occurs in severely premature neonates who have undergone repeated traumatic attempts at endotracheal intubation or passage of orogastric tubes. It may also mimic esophageal atresia (EA). Perforation of upper pouch in tracheoesophageal fistula with EA was rarely reported. We report a 1,400 g (32 weeks) neonate with pure EA and iatrogenic perforation of upper pouch due to use of catheter for diagnostic radiography.